KOMUNIKASI PEMBANGUNAN KELUARGA KELURAHAN ANGKE DALAM MENINGKATKAN KEHIDUPAN MASYARAKAT (Studi Kasus : Ruang Publik Terpadu Ramah Anak Kalijodo) - Helen Olivia (Jurnal Komunikasi, 2020)
Abstrack – Jakarta is one of the big cities that has a high level of economy. Unfortunately not yet accompanied by the many natural attractions and families. Child Friendly Public Spaces, hereinafter abbreviated as RPTRA, are places and or open spaces that integrate activities and activities of citizens by implementing 10 Principal Empowerment and Family Welfare programs to integrate with the Child Friendly Cities program. The purpose of this study is to discuss the efforts made in improving the communication relationship of Angke Village PKK development with the community. In this study researchers used qualitative research methods. Data collection techniques used in research are in-depth interviews and non-participant observation to collect primary data, as well as literature studies and documentation to obtain secondary data. The results of this study indicate that the Development Communication carried out by the Angke Village PKK and the Kalijodo RPTRA Manager in the utilization of the Kalijodo RPTRA in the field of education and skills have a positive impact on society.Keywords: Development Communication, RPTRA, PKK